Novel targets and therapies of metformin in dementia: old drug, new insights - Cui, Wenxing; Lv, Chen; Geng, Panling; Fu, Mingdi; Zhou, Wenjing; Xiong, Mingxiang; Li, Tian (Frontiers in Pharmacology, 2024)
Dementia is a devastating disorder characterized by progressive and persistent cognitive decline, imposing a heavy public health burden on the individual and society. Despite numerous efforts by researchers in the field of dementia, pharmacological treatments are limited to relieving symptoms and fail to prevent disease progression. Therefore, studies exploring novel therapeutics or repurposing classical drugs indicated for other diseases are urgently needed. Metformin, a firstline antihyperglycemic drug used to treat type 2 diabetes, has been shown to be beneficial in neurodegenerative diseases including dementia. This review discusses and evaluates the neuroprotective role of metformin in dementia, from the perspective of basic and clinical studies.Mechanistically, metformin has been shown to improve insulin resistance, reduce neuronal apoptosis, and decrease oxidative stress and neuroinflammation in the brain. Collectively, the current data presented here support the future potential of metformin as a potential therapeutic strategy for dementia. This study also inspires a new field for future translational studies and clinical research to discover novel therapeutic targets for dementia.